Expectant versus active management in term prelabor rupture of membranes (PROM) - a prospective study in a tertiary care hospital - Arnab Berma; Amita Ray; Nrityendra Narayan Bhattacharya; Koushik Basu; Bharath Kumar; Sougato Kumar Sarkar (Barpeta Obstetrics and Gynaecological Society, 2019)
Objectives: This study was done with the main objectives of assessing the prevalence, identifying the associated factors and comparing feto-maternal outcomes in expectant versus active management in term PROM. Methods: This was a prospective cohort study where two convenience groups were categorized as expectant and active management with feto-maternal morbidities and mode of delivery as outcomes of interest. Further, the active group was categorized into two groups one of which received oxytocin and the other received a combination of prostaglandins and oxytocin. Here the main outcome of interest was the mode of delivery. The statistical software "R" was used to calculate the odds-ratios, 95% C.I. and p-values. Results: Prevalence of PROM was 16.7% and apart from multiparity (p=0.0467) none of the other factors were significantly associated with term PROM. Maternal infective morbidity was significantly more in the expectant management group (p=0.001) with no significant difference in the C-Section rates (p= 0.906) and neonatal morbidity (p=0.4). Active management with oxytocin and prostaglandins resulted in a significantly higher number of vaginal deliveries (p< 0.001) when compared to the only oxytocin group. Conclusion: Expectant management did not result in significantly higher operative deliveries or increased neonatal morbidity. Using prostaglandin with oxytocin gave a better result than oxytocin alone in terms of vaginal delivery.